Analysis of The Reliability Index of The Platuk Feeder Distribution System at PT. PLN ULP Kenjeran with Section Technique Method - Reza Sarwo Widagdo; Gatut Budiono; Puji Slamet; Muhammad Sultan Abdai Habibullah (Jurnal Riset Rekayasa Elektro, 2024)
A high success rate is required to ensure the continuity of the supply of electricity, so that the distribution of electricity can maintain its availability continuously and have a reliable reliability value. Therefore, this study is intended to help evaluate the reliability of electric power distribution in plate feeders at PT. PLN ULP Kenjeran. The effect of failure on the system caused by equipment failure, as well as its impact on the load point will be evaluated using the section technique method. The results of the calculation show that the value of SAIFI is 2,699 times/year, SAIDI is 5.128 hours/year, and CAIDI is 1.9 hours/disturbance. Based on SPLN No. 68-2: 1986 concerning the reliability index, the value of SAIFI is 3.2 times/year, SAIDI is 21 hours/year, and CAIDI is 6.56 hours/disturbance, where the reliability index value can be categorized in accordance with SPLN standards and is considered reliable. Meanwhile, in the comparison of calculations between the section method and the method without sections, the reliability results were worse. Where the SAIFI value was 3.21112 times/disturbance (up 15.93%), the SAIDI value was 12.4056 hours/year (up 58.65%), and the CAIDI value was 3.9 hours/interruption (up 51.12%). Efforts to improve reliability by improving preventive maintenance and adding switching equipment such as LBS